A critical analysis on electro-mechanical works of public works department based on key performance indicators to comply PPA 2006 & PPR 2008 - Fatema, Kanij (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.